2018
DOI: 10.1155/2018/9192104
|View full text |Cite
|
Sign up to set email alerts
|

Update of ALDH as a Potential Biomarker and Therapeutic Target for AML

Abstract: Studies employing mouse transplantation have illustrated the role of aldehyde dehydrogenase (ALDH) defining hematopoietic stem cells (HSCs) and leukemia stem cells (LSCs). Besides being a molecular marker, ALDH mediates drug resistance in AML, which induces poor prognosis of the patients. In AML patients, either CD34+ALDHbr population or CD34+CD38−ALDHint population was found to denote LSCs and minimal residual disease (MRD). A bunch of reagents targeting ALDH directly or indirectly have been evaluated. ATRA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 48 publications
(58 reference statements)
1
13
0
Order By: Relevance
“…These processes are involved in the prognosis of AML. [25][26][27] Moreover, CD133 expression is highly associated with chemoresistance and prognosis of patients with AML. 28 Our results showed that AKAP9 silencing decreases the expression of ALDH1A1 and CD133 in AML cells.…”
Section: Discussionmentioning
confidence: 99%
“…These processes are involved in the prognosis of AML. [25][26][27] Moreover, CD133 expression is highly associated with chemoresistance and prognosis of patients with AML. 28 Our results showed that AKAP9 silencing decreases the expression of ALDH1A1 and CD133 in AML cells.…”
Section: Discussionmentioning
confidence: 99%
“…Acute myeloid leukemia (AML) is the most common type of myeloid malignancy in adults, and with the exception of the acute promyelocytic leukemia (APL, M3) subtype, this disease has an overall poor prognosis with limited change in the standard of care [1,2]. In leukemic environments, regulatory T cells (Tregs) contribute to immune escape by suppressing antileukemia activity, and these cells include multiple T cell subsets that control the immune response through a variety of mechanisms [3].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, deregulation of RA signaling is one of the hallmarks of carcinogenesis and autoimmune diseases [169,170]. In this context, ALDHs activity may be considered not only as a prognostic marker but also as a potential therapeutic target [171][172][173][174]. In fact, compelling evidence indicates the ALDHs involvement in regulation of cell proliferation, survival, and chemoresistance of cancer stem cells [175,176].…”
Section: Unidirectional Production Of Retinoic Acidmentioning
confidence: 99%